Convulsive Status Epilepticus in Children: A Prospective Observational Study from India - Arya, Adhi; Azad, Chandrika; Mahajan, Vidushi; Guglani, Vishal (Journal of Pediatric Epilepsy, 2020)
Convulsive status epilepticus (CSE) is one of the commonest and life threatening pediatric neurological emergencies. Only few studies on pediatric status epilepticus (SE) are available from the Indian subcontinent. The aim was to study the etiology and immediate outcome of CSE in children getting admitted in pediatric emergency during the study period and to study association of various clinical presentations with immediate outcome. A prospective observational study was conducted in tertiary care institute of Northern India. Children aged between 1 month and 18 years with CSE were enrolled and followed up till discharge. Primary outcome was kept as hospital survival/mortality; those who survived were further graded on the basis of disability at discharge. A total of 81 patients with CSE were assessed for primary outcome. The mortality rate was found to be 15% (12/81); 83% deaths were due to acute central nervous system (CNS) infection. Ten percent of children (8/81) had disability at discharge, five had mild, and three had moderate disability. The neurocysticercosis was the most common etiology seen in 23% (19/81) of the children followed by febrile SE in 20% (13/81) of the study participants. CSE responded to first-line antiepileptic drugs (AED) in 15% children (12/81). Refractory status was seen in 13.5% (11/81) cases. Prehospital treatment was received only in 15% patients. Young age, low Glasgow coma scale score at admission, and requirement of critical care support were the factors found to be significantly associated with mortality. CSE has a high mortality especially in young children and acute CNS infections are the most common cause of it.
Keywords: convulsive status epilepticus; children; outcome